أثر التحول الحضري للمجتمع القصوري على الممارسات الاجتماعية دراسة حالة مدينة بسكرة - تابعي, إبراهيم; علقمة, جمال (Courrier du Savoir; No 26 (2018): Courrier du Savoir, 2018)
The Arab Maghreb countries and Algeria as a part of them were subjected to contradictions that tilted their balance as the beginning of the French occupation and the implementation of its projects. It resulted in a hybrid architectural and urban product which gathers between the Arab Islamic city and the European city by reconstructing new cities with new building logic differs to the traditional urbanconstruction, so that the reconstruction of the occupation could be regarded as the first seed in the change of the centrality that was represented in the palace. The current general view of the Algerian city and in particular Biskra city- as it is our case study- has no links with the city’s heritage that it was inherited through the generations either at the architectural and the urban level or at the social and the cultural level. Accordingly, the original architectural and traditional social practices have disappeared. The interested observer can see clearly today's society changes. It has been overwhelmed by a set of material values based on concrete material elements and disregarding the spiritual values springing from the religious instructions, customs and moral principles. Therefore, a range of social practices derived mainly from materialistic preferential values appeared in the first place. These values serve the desires of man emerging from the material reality surrounding the contemporary individual. These new social practices alongside the linked set of values is undoubtedly considered a power affecting the social relations among the family members and among the community through reorganizing the relations and move them from the basis of gender-based and age-based foundations to the democratic foundations based on competence and eligibility.